The influence of social media usage, destination personality, destination image and self congruity on behavioural intention to Visit Labuan Bajo - Atmaja, Ivan Surya; Bernarto, Innocentius (Enrichment : Journal of Management, 2024)
The tourism sector in Indonesia still has a low contribution to gross domestic income compared to other countries in ASEAN; therefore, the tourism sector in Indonesia has the potential to continue to be developed and, of course, can contribute more to the economy. This research analyses the influence of social media use, destination personality, destination image and self-congruity on behavioural intention to visit Labuan Bajo. This research was conducted on 173 respondents who had visited tourist attractions in Labuan Bajo. The method used is quantitative with the SEM-PLS analysis technique. The research results show that the use of social media, destination personality and self-congruity can influence behavioural intention to visit Labuan Bajo significantly and positively. However, destination image cannot significantly influence behavioural intention to visit.